Facebook as a Public Space for Discussing Political Issues in Algeria: Algerian Popular Movement as a Model. - Wisseme BELHADI; Lyes TALEHA (International Journal of Social Communication, 2024)
This research is conducted within a descriptive-analytical framework, scrutinizing the role of Facebook as a dynamic virtual public sphere in navigating and orchestrating discourse on diverse political matters, as well as in identifying the pivotal stakeholders involved. Uniquely, Facebook transcends traditional boundaries, embracing a myriad of social layers instead of catering exclusively to specific societal groups. A defining feature of this virtual arena is its emancipation from traditional media’s ‘gatekeeper’, offering an unparalleled level of freedom. This attribute was particularly evident during the Algerian popular movement, as activists exploited various expressive avenues through Facebook, both in support of and opposition to the movement. This platform not only amplified discussions on myriad pertinent issues but also served as a conduit for the movement’s oscillation between virtual and tangible realities. This transformation saw demonstrators employing Facebook not only to interpret real-world scenarios but also to forecast forthcoming developments, a phenomenon that this study will explore in-depth.